Innate immune signaling and regulation in cancer immunotherapy - Corrales, Leticia (Cell Res, 2017)
A pre-existing T cell-inflamed tumor microenvironment has prognostic utility and also can be predictive for response to contemporary cancer immunotherapies. The generation of a spontaneous T cell response against tumor-associated antigens depends on innate immune activation, which drives type I interferon (IFN) production. Recent work has revealed a major role for the STING pathway of cytosolic DNA sensing in this process. This cascade of events contributes to the activation of Batf3-lineage dendritic cells (DCs), which appear to be central to anti-tumor immunity. Non-T cell-inflamed tumors lack chemokines for Batf3 DC recruitment, have few Batf3 DCs, and lack a type I IFN gene signature, suggesting that failed innate immune activation may be the ultimate cause for lack of spontaneous T cell activation and accumulation. With this information in hand, new strategies for triggering innate immune activation and Batf3 DC recruitment are being developed, including novel STING agonists for de novo immune priming. Ultimately, the successful development of effective innate immune activators should expand the fraction of patients that can respond to immunotherapies, such as with checkpoint blockade antibodies.